Combination of Intravitreal Bevacizumab and Topical Dorzolamide versus Intravitreal Bevacizumab Alone for Diabetic Macular Edema: A Randomized Contralateral Clinical Trial. (17th January 2020) - Fazel, Farhad; Nikpour, Hossein; Pourazizi, Mohsen
Abstract : Purpose . To evaluate the efficacy of three intravitreal bevacizumab (IVB) injections versus the same combined with 2% of topical dorzolamide in the treatment of diabetic macular edema (DME). Methods . In this randomized double-masked clinical trial, 32 eyes of 16 treatment-naive patients with bilateral DME were enrolled. The eyes were randomly assigned to receive three monthly injections of IVB (1.25 mg) plus topical dorzolamide 2% twice daily or IVB (1.25 mg) plus topical artificial tear twice daily. Best-corrected visual acuity (BCVA) was the primary outcome of the study followed by the central macular thickness (CMT) and central macular volume (CMV) as the secondary outcomes. Results . Mean BCVA changes were insignificant in both groups. It changed from 0.21 ± 0.08 logMAR at baseline to 0.23 ± 0.09 (P = 0.24 ) in the combination group and from 0.18 ± 0.09 logMAR to 0.21 ± 0.09 (P = 0.11 ) in the IVB alone group, at 3 months, respectively. Changes in mean CMT and CMV were significant in both groups. However, the difference between the groups was not significant at all the visits. In the study, no major ocular complication or systemic side effects were noted regarding IVB or topical dorzolamide. Conclusion . This randomized contralateral clinical trial demonstrated that adjuvant topical dorzolamide with IVB injection had no additional effects on IVB in the treatment of DME over a three-month course. This trial is registered with the Iranian Registry of Clinical Trials under the registration code IRCT20131229015975N5 .